Natural Compounds in Guava (Psidium guajava) Leaves: A Phytochemical Study - Mustapha, Musa Azegya; A, Arowora K.; S, Ezeonu C.; Umaru, Isaac John (Kwaghe International Journal of Sciences and Technology, 2025)
This study investigates the chemical composition and hepatoprotective potential of ferrous nanoparticles (FeNPs) synthesized from Psidium guajava (Linn.) leaf extract, focusing on their effects on liver function in male Wistar rats. Fresh leaves of P. guajava were collected from the Government Reservation Area (G.R.A), Wukari, Taraba State, Nigeria, washed, air-dried, and pulverized for analysis. The resulting leaf powder was subjected to phytochemical screening, vitamin profiling, and mineral composition analysis, while the synthesized FeNPs were characterized using UV–visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), and gas chromatography–mass spectrometry (GC–MS). GC–MS analysis revealed a rich profile of bioactive compounds, with 2-hexyl-1-octanol identified as the most abundant constituent. Vitamin profiling showed a high concentration of folate (65.10%), moderate levels of thiamine (32.90%), and trace amounts of vitamin E (1.40%) and vitamin K (0.60%). Mineral analysis indicated potassium (9.40 ± 0.89 ppm) as the predominant element among the five minerals detected. UV–visible spectroscopy confirmed the successful synthesis of FeNPs, evidenced by a characteristic absorption peak at 360 nm, while FTIR analysis identified functional groups such as hydroxyl (O–H), alkane (C–H), and alkene (C=C), suggesting the presence of phytochemicals capable of reducing and stabilizing the nanoparticles. Overall, the findings demonstrate that Psidium guajava leaf extract is a rich source of vitamins, minerals, and phytochemicals that effectively mediate the green synthesis of ferrous nanoparticles, and that the presence of bioactive compounds and functional groups supports the potential of these FeNPs for biomedical applications, particularly in liver function modulation. This study provides a foundational basis for further exploration of the therapeutic efficacy and safety of guava leaf-derived nanoparticles in hepatoprotection and other health-related interventions.